Player's handbook - Crawford, Jeremy; Wyatt, James, 1968-; Schwalb, Robert J.; Cordell, Bruce R. (Wizards of the Coast LLC, 2014)
An essential reference for every Dungeons & Dragons roleplayer, this text contains rules for character creation and advancement, backgrounds and skills, exploration and combat, equipment, spells, and much more.